2020
DOI: 10.3390/su12093910
|View full text |Cite
|
Sign up to set email alerts
|

Corporate Economic, Environmental, and Social Sustainability Performance Transformation through ESG Disclosure

Abstract: Within the environmental, social, and governance (ESG) disclosure–corporate sustainability performance (economic, environmental and social; EES) framework, our empirical analysis examined the impact of ESG information disclosure on EES sustainability performance among Asian firms from 2005 to 2017. The positive ESG disclosure–EES sustainability performance relationship found in this study provides evidence that disclosing the implementation of environment and social strategies within an effective system of cor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

15
288
1
7

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 385 publications
(311 citation statements)
references
References 66 publications
15
288
1
7
Order By: Relevance
“…This paper seeks to establish whether a firm's environmental performance is influenced by its governance mechanisms in terms of its ownership structure and its board of directors. Environmental performances are one of the four points of reference according to which corporate social responsibility (CSR) outcomes are classified [50,110]. Another type of CSR outcome classified as social performance is corporate responsibility aimed at multiple stakeholders and this is measured through stakeholder involvement, philanthropic activity, respect for ethical codes and the law, and assessment of the impact on stakeholders.…”
Section: Discussionmentioning
confidence: 99%
“…This paper seeks to establish whether a firm's environmental performance is influenced by its governance mechanisms in terms of its ownership structure and its board of directors. Environmental performances are one of the four points of reference according to which corporate social responsibility (CSR) outcomes are classified [50,110]. Another type of CSR outcome classified as social performance is corporate responsibility aimed at multiple stakeholders and this is measured through stakeholder involvement, philanthropic activity, respect for ethical codes and the law, and assessment of the impact on stakeholders.…”
Section: Discussionmentioning
confidence: 99%
“…It indirectly reflects that the company’s environmental performance has received the attention of the Chinese government. Alsayegh et al found that environmental performance and social performance are significantly positively correlated with economic sustainability performance, indicating that the economic value of enterprises and socially created value are interdependent [ 1 ], and it also provides a theoretical support for the government to attach importance to corporate environmental performance.…”
Section: Introductionmentioning
confidence: 99%
“…(2020), in the paper"Beyond COVID-19 Pandemic: A Systematic Review of the Role of Global Health in the Evolution and Practice of Corporate Social Responsibility", studied the impact of the COVID-19 on CSR and concluded that the call for a radical overhaul of health and safety measures in enterprises is now urgent than ever before. Alsayegh, et al, (2020) studied "Corporate Economic, Environmental, and Social Sustainability Performance Transformation through ESG Disclosure" studied that disclosing the implementation of environmental and social strategies within an effective system of corporate governance in the organization strengthens corporate sustainability performance. They concluded that ESG information disclosure to all stakeholders is a vital factor in creating a competitive advantage for enhancing corporate sustainability performance.…”
Section: Review Of Literaturementioning
confidence: 99%